2022
DOI: 10.1590/1516-4446-2020-1576
|View full text |Cite
|
Sign up to set email alerts
|

Faith-based intervention, change of religiosity, and abstinence of substance addicts

Abstract: Objective: To investigate the effects of developing religiosity on abstinence of substance abuse among recovering addicts in a faith-based and a secular-based treatment program. Methods: Religiosity of recovering addicts was measured using the 38-item Brief Multidimensional Measure of Religiousness/Spirituality at three points in time: at initiation of substance addiction treatment (wave 1), discharge from treatment (wave 2), and 6 months after treatment (wave 3). Latent growth curve modeling was used to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…The research also affirms that when religious groups participate, the programs produce positive results, further highlighting the crucial role of religious groups in social recovery (Kabore et al, 2019). Moreover, in a study conducted by Yeung (2022), it was observed that religious involvement played a significant role in helping recovering addicts. This assistance is evident in aspects such as finding life meaning and purpose and improving interpersonal relationships.…”
Section: Social Networksupporting
confidence: 65%
See 2 more Smart Citations
“…The research also affirms that when religious groups participate, the programs produce positive results, further highlighting the crucial role of religious groups in social recovery (Kabore et al, 2019). Moreover, in a study conducted by Yeung (2022), it was observed that religious involvement played a significant role in helping recovering addicts. This assistance is evident in aspects such as finding life meaning and purpose and improving interpersonal relationships.…”
Section: Social Networksupporting
confidence: 65%
“…The influence of the partner or significant other is evident in providing solid support and brings positive impact to drug addicts (Yeung, 2022). Individuals who do not have a partner are more likely to experience loneliness and hopelessness in moving on with life (Yeung, 2022).…”
Section: Role Of Partner/significant Othermentioning
confidence: 99%
See 1 more Smart Citation